Trans-migrants in Mexico - Kos-Stanišić, Lidija (Teorija in praksa, 2018)
This article attempts to investigate and probe the 2014 Central American Refugee crisis and the communications made on the social media Twitter. It does so by first illustrating the factors that motivate people to migrate from Guatemala, El Salvador and Honduras and explains the context of Mexico's changing policies on migrants. In the second part, a brief analysis of Twitter communications around the (trans)migration crisis and new policy implementation is conducted using big data software.
Keywords: Begunci; Communication; Družbeni mediji; International migration; Javna politika; Komuniciranje; Mednarodne migracije; Public policy; Refugees; Social media